2020
DOI: 10.1093/jipm/pmz037
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Challenges of Dealing with Citrus Greening: The Case of Florida

Abstract: While pest management decisions are made at the farm level, a distinctive characteristic of the pest management of invasive species is its public-good nature. Here, we examine the challenges that a vector-disease pathosystem such as Diaphorina citri Kuwayama (Hemiptera: Liviidae)—citrus greening, creates for the adoption of prevention and collective management practices from an economic perspective. Those economic challenges originate from the choices and behavior of individual growers, which can impact not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 48 publications
0
58
0
1
Order By: Relevance
“…The intensifying insecticide application also creates environmental and public health concerns and side-effects to specific fauna, as the arthropod (Monzo and Stansly, 2017). Singerman and Page (2016) indicated that CHMAs enhance grower's profitability when all growers involved participated in the program.…”
Section: Huanglongbing Control and Mitigation Of Its Symptomsmentioning
confidence: 99%
“…The intensifying insecticide application also creates environmental and public health concerns and side-effects to specific fauna, as the arthropod (Monzo and Stansly, 2017). Singerman and Page (2016) indicated that CHMAs enhance grower's profitability when all growers involved participated in the program.…”
Section: Huanglongbing Control and Mitigation Of Its Symptomsmentioning
confidence: 99%
“…The African citrus psyllid Trioza erytreae (del Guercio, 1918; Hemiptera: Triozidae) is a natural vector of the phloem-limited Gram-negative bacterium Candidatus liberibacter spp., the putative causal agent of huanglongbing (HLB) or “citrus greening disease” [ 11 , 12 ]. HLB is an incurable disease that caused losses of up to 74% in citrus production in Florida, USA [ 13 ]. Trioza erytreae was detected in the northwestern Iberian Peninsula in 2014 [ 14 ], although it was present in Madeira and the Canary Islands by 1994 and 2002, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also known as the Asian citrus psyllid, D. citri is a hemipteran insect pest and serves as a vector of Candidatus Liberibacter species that cause Huanglongbing, or citrus greening disease, in all types of commercially cultivated citrus (28). This disease represents the greatest threat to the citrus industry worldwide and has devastated many citrus-growing regions, such as in the U.S. state of Florida, where citrus production has decreased by 74% since the first report of citrus greening disease in the state in 2005 (29). Control strategies for the disease are limited and primarily involve removal of infected trees and management of D. citri populations with chemical insecticides (30).…”
mentioning
confidence: 99%